2017
DOI: 10.1364/oe.25.010677
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton imaging with blue-diode-pumped SESAM-modelocked Ti:sapphire oscillator generating 5 nJ 82 fs pulses

Abstract: We report a directly blue diode pumped Ti:Sapphire oscillator that generates 5 nJ pulses. This is five times higher pulse energy than previously reported for a directly diode pumped Ti:sapphire laser. With 460 mW of average power at 92 MHz and 82 fs pulses, its peak power reaches 61 kW, also several times higher the value than previously published. Direct diode pumping significantly reduces the complexity and therefore the footprint and the cost of the laser, while SESAM modelocking ensures reliable selfstarti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Moreover, all current works have done based on such a model. Since 2009, the performance of LD-pumped Ti:sapphire lasers has been gradually improved, approaching the performance of traditional Ti:sapphire lasers in terms of high power, [59][60][61][62] wide wavelength tunability, 61,63 and short pulse duration. [64][65][66][67][68] 3.1 | Blue-laser-diode pumped Ti:sapphire oscillators…”
Section: Laser-diode Pumped Ti: Sapphire Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all current works have done based on such a model. Since 2009, the performance of LD-pumped Ti:sapphire lasers has been gradually improved, approaching the performance of traditional Ti:sapphire lasers in terms of high power, [59][60][61][62] wide wavelength tunability, 61,63 and short pulse duration. [64][65][66][67][68] 3.1 | Blue-laser-diode pumped Ti:sapphire oscillators…”
Section: Laser-diode Pumped Ti: Sapphire Lasersmentioning
confidence: 99%
“…In 2017, Rohrbacher et al employed two 2.9 W 450 nm blue LDs to bilaterally pump a 4 mm long Ti: sapphire crystal, and used a SESAM to start and maintain the mode-locking operation. 60 The mode-locked oscillator could obtain a maximum output power of 460 mW with 82 fs pulse width. The optical-to-optical conversion efficiency of blue LD directly pumped Ti:sapphire mode-locked laser is close to 8%.…”
Section: Laser-diode Pumped Ti: Sapphire Lasersmentioning
confidence: 99%
“…In this case, three different excitation spectra can be generated, centered at three different wavelengths [164]. Mahou et al [68] have demonstrated the simultaneous acquisition of three colors using two spatially and temporally synchronized pulse trains.…”
Section: 1a Simultaneous Multicolor Detectionmentioning
confidence: 99%
“…In addition, using near infrared (NIR) excitation wavelengths also increases the penetration depth, which is particularly significant for biomedical imaging [10][11][12]. Multiphoton microscopy (MPM) and coherent Raman scattering (CRS) microscopy are the most frequently applied nonlinear imaging technologies for biomedical microscopy [13][14][15][16][17][18]. The former mainly includes two-photon fluorescence (TPF), three-photon fluorescence (ThPF), second-harmonic generation (SHG), and third-harmonic generation (THG) microscopy.…”
Section: Introductionmentioning
confidence: 99%